BISNIS KREATIF DI ERA DIGITAL DENGAN MENGANGKAT KEARIFAN LOKAL - Ni Made Sri Wahyuni Trisna; Farriz Fardani Zulkifli (Jurnal Da Moda, 2021)
Creative business in this digital era is one of the ways to bring in fixed income as well as side income, but many people also can't see that creative business in this digital era is very easy to do and there are many ways, especially by raising local wisdom products that are is all around us. Many cannot see the potential of local wisdom products that are around us, especially in Bali. even these products can be marketed on a national and international scale very easily in this digital era. The appeal of products containing local Balinese wisdom is very popular with many circles, and can be a new hope for many people who want to be involved in creative business in the digital era.